Analisis Kualitas Layanan Aplikasi Ruangguru dengan E-Servqual dan Net Promoter Score (NPS) - Wafa Subchan; Moch. Tutuk Safirin (Limits: Journal of Mathematics and Its Applications, 2025)
Digital transformation in the education sector has led to an increase in the use of online learning applications such as Ruangguru. Ruangguru is an online learning platform, which offers various digital products to support the learning process and provide a more interactive learning experience. However, meeting customer satisfaction and gaining user loyalty are key challenges in digital service development. This study aims to analyze the service quality of the Ruangguru application using the e-servqual approach which has seven dimensions, efficiency, fulfillment, reliability, privacy, responsiveness, compensation, and contact, to identify areas of improvement needed, as well as the Net Promoter Score (NPS) method to determine customer loyalty in using the Ruangguru application. Data was collected through questionnaires to 100 respondents who use the Ruangguru application. The results show that there is a gap between customer perceptions and customer expectations with a negative value, which indicates that the Ruangguru application has not met user expectations. The NPS value obtained from the formula calculation is 21, which indicates the level of customer loyalty is within the loyal parameter.